Influences of deglaciation on the river run-off in Central Asia - G. E. Glazyrin (Лëд и снег, 2015)
Glaciers form a great deal of runoff of rivers in Central Asia. It is clear that amount of melted water directly depends on total area of glaciers in the river basins – their glaciation. It is well known that at present the area quickly reduces. The complete inventory of glaciers was performed in former Soviet Union in the middle of last century. Airphoto images were used as a basis for our calculations. The inventory was repeated later for several river basins using airphoto- and space images. Unfortunately only three inventories is performed in several river basins for the last half of XX century. Amount of water, coming to a river network from glaciers, can be divided into two parts. The first is usual annual melting. It exists under stationary glaciation condition. The second, being part of the first, is caused by reduction of the glaciation volume. It can be negative in some years when glaciers volume is increasing as a result of favorable meteorological conditions. In these cases the part of water containing in seasonal snow cover does not go to river network. Two components of the glacial feeding were calculated for six rivers located in various regions of Central Asia. It is shown that present day glaciers reduction does not lead to disastrous consequences for river run-off. It leads only to the changes of annual distribution in the run-off. The results should be considered as preliminary because of low accuracy of hydrometeorolological data and number of admissions during calculation.